(3GdeOhfIs - (3CHh YHO Gddg YHO GdQMef GHf GdbGSe GdeGdcj,J (B191 (3g` s ((3eMeO GdeOYh MLGRj GdbdJj GdeGdcj s)
(3ChdgG (B:s
(3Mbge bGd CeG GdYHO hGdeQCI afYe jMdahf hjSJMbhf hGeG GdUHj adG jMda MJi jcHQ s
(3BNQgG (B:s
(3Je cJGH GdLQGeGJ ef GdeOhfI HMeO Gddg hYhfg hMSf Jhajbg hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3CHhGH ef GdHjhY hGdoeYGedGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1644s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs